Lattice dynamics of cryocrystals at high pressure - Horbenko, E.E.; Troitskaya, E.P.; Chabanenko, Val.V. (Физика низких температур, 2007)
The lattice dynamics of cryocrystals is investigated from first principles in the framework of the Tolpygo
model over a wide range of pressures. The phonon frequencies in rare-gas solids are calculated in terms of
models that go beyond the scope of adiabatic approximation. At high pressure the phonon spectrum along
the Δ and Σ directions is distorted and the longitudinal L- and transverse T₂-modes soften as a result of the
electron–phonon interaction, with the relative contribution decreasing in the sequence Ar, Kr, Xe. The calculated
phonon frequencies are in good agreement with the experimental data for argon crystals of a pressure
3.1 GPa.